A representação das masculinidades em textos de Lygia Bojunga - Magalhães, Rosânia Alves (2019)
This research consists of verifying the representation of masculinities in the narratives of Lygia Bojunga, namely, Tchau (1984), Seis vezes Lucas (1994), and Sapato de salto (2006). For that, the theoretical formulations on the concept of gender and masculinity, androcentrism and misogyny are analyzed, hegemonic and subordinate masculinity and symbolic violence, highlighted by Robert W. Connell, Pierre Bourdieu, Pedro Paulo de Oliveira, Elizabeth Badinter, among others. From these discussions, it is sought to understand the symbolic violence from the choice of male characters with misogynistic characteristics in the narratives of Lygia Bojunga. It is hypothesized that the author discusses in her narratives the question of misogyny within contemporary society, demonstrating a systematization based on the hegemony of the masculine that privileges the masculine in detriment of the feminine. This analysis is based on conceptions about children’s literature and, above all, gender issues. Thus, the different types of masculinities presented by the author favor the reader, especially the youth public, alternatives in the construction of new paths, different from those established and naturalized by the patriarchal model of masculinity.